Stage description, new combination and new records of Neotropical Brachycercinae (Ephemeroptera: Caenidae) - Angeli, Kamila Batista (2016)
We present taxonomic contributions and new records for Neotropical Brachycercinae based on material from Brazil. We performed a phylogenetic analysis in order to test the relationship between Alloretochus Sun & McCafferty, 2008 and Latineosus Sun & McCafferty, 2008, and Alloretochus sigillatus was recovered in the Latineosus clade. Therefore, we propose a new combination, Latineosus sigillatus comb. N. The nymph of Latineosus sigillatus is described and is associated with imago through molecular tools. Moreover, Alloretochus peruanicus (Soldán, 1986) is reported for the first time from Brazil.